(untitled) (Research, Society and Development, 2020)
This text presents the results of a research carried out in the Strictu Sensu Postgraduate Program, whose objective was to analyze the teaching practices of two teachers in the early years of Elementary School (PE) when they teach Portuguese Language and Science, seeking to detect whether there is or non-convergences in approaches to content and methodologies for science education with progressive characteristics of literacy from the perspective of literacy. With a qualitative approach, the research deals with a case study, in which the teaching practice of teachers was observed, using the field diary and video recording as a recording instrument. The results of the research indicate that although the teachers consider the students’ socio-cultural environment, and mobilize several didactic strategies in the classroom, they develop a practice anchored in the principles of the traditional trend. In addition, the research signals that the teaching of Natural Sciences has not been valued in the same way as that of the Portuguese Language and suggests that an expansion of the concept of literacy that encompasses Science Teaching and resignifies itself with the notions of scientific literacy since the children’s literacy.